Low health-related quality of life is strongly linked to upper extremity impairments in type 1 diabetes with a long duration. Issue 18 (28th August 2021) - Gutefeldt, Kerstin; Hedman, Christina A.; Thyberg, Ingrid S. M.; Bachrach-Lindström, Margareta; Arnqvist, Hans J.; Spångeus, Anna
Abstract: Purpose: To compare health-related quality of life (HRQOL) in type 1 diabetes and non-diabetic controls and possible links to upper extremity impairments (UEIs). Prevalence of sick-leave and causes were investigated. Materials and methods: This Swedish population-based case-control study included type 1 diabetes patients <67 years old and with a diabetes duration ≥20 years. Participants completed a postal questionnaire including Short Form 36, and questions regarding UEIs, and sick-leave. Results: In total, 773 patients, aged 50 ± 10 years (diabetes duration 35 ± 10 years), and 708 non-diabetic controls, aged 54 ± 9 years, completed the study. Patients reported significantly lower HRQOL compared with controls. The difference was greatest for general health, vitality, and bodily pain. Patients with shoulder or hand but not finger impairments scored significantly lower than asymptomatic patients. The prevalence of sick leave was higher in patients vs. controls (23% vs. 9%, p < 0.001), and nearly half cited impairments from back, muscles, or joints as the main reason. Conclusions: Health-related quality of life is lower in type 1 diabetes than controls and in patients with shoulder and hand impairments than in asymptomatic. Musculoskeletal impairments (back/muscle/joints) have impact on work ability. Identification of UEIs is important for initiating preventative-, therapeutic-, and rehabilitative interventions. Implications for rehabilitation: Upper extremity impairments (UEIs) that are common in type 1 diabetes, and associated with reduced health-related quality of life, should preferably be screened for on a regular basis along with other known diabetes complications. Early identification of UEIs is important to improve health by initiating preventive as well as therapeutic multi-professional rehabilitative interventions. Sick leave is higher in type 1 diabetes than in controls. Musculoskeletal impairments, including the back, muscles, and joints, are a common cause for sick leave warranting further studies.